The critical analysis of religious diversity - Kühle, Lene. (International Studies in Religion and Society, 2018)
Drawing on international and thematic case studies, The Critical Analysis of Religious Diversity asks its readers to pay attention to the assumptions and processes by which scholars, religious practitioners and states construct religious diversity. The study has three foci: theoretical and methodological issues; religious diversity in non-Western contexts; and religious diversity in social contexts. Together, these trans-contextual studies are utilised to develop a critical analysis exploring how agency, power and language construct understandings of religious diversity. As a result, the book argues that reflexive scholarship needs to consider that the dynamics of diversification and homogenisation are fundamental to understanding social and religious life, that religious diversity is a Western concept, and that definitions of 'religious diversity' are often entangled by and within dynamic empirical realities.